Design and implementation of material characteristics for capacitive coupling wireless power transfer system - Kannan, R. (Research India Publications, 2017)
This research work describes a design and implementation of materials characteristics for the capacitive coupling wireless power transfer system. There were two types of Wireless Power Transfer (WPT) that have widely been used and studied by researchers: Inductive Power Transfer (IPT) and Capacitive Power Transfer (CPT). Electric fields transmit by the electrostatic induction phenomena between transmitter and receiver.A capacitor is formed at the transmitter and receiver with the intervening space as the dielectric. The transmitter generates an alternating voltage that is applied on transmitter plate from primary circuit. The alternating potential is induced by the oscillating electric field on the receiver plate by electrostatic inductions which cause the alternating current to flow in the secondary circuit. In this research, two types of the materials are used as the transmitter and receiver plate; aluminum plate and a zinc plate. With the fix distance of the air gap, variable size of the plate, variable thickness of the plate and also the variable thickness of the glass, the power transfer has been measured. Improvements: The thickness of the plates does not affect the power transfer. The conductivity of the electricity of the plates in the different thickness gives the same capability to carry electron. © Research India Publications.